2018
DOI: 10.21082/blpn.v24n2.2018.p125-134
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin Content Characterization on Pigmented Local Rice as Genetic Resources of Functional Food

Abstract: <p>Local varieties of pigmented rice are highly valuable genetic resources as a functional food in the future. Pigmented rice contains anthocyanins which function as nutrient bioactive components, called antioxidants. The aim of this research was to characterize anthocyanin content on 27 accessions of pigmented local rice, 2 varieties of released red rice varieties (Aek Sibundong and Inpari<br />24), and 1 control varieties of white rice, Ciherang. The content of anthocyanin was analyzed by using H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
3
0
3
Order By: Relevance
“…The Jeliteng cultivars are known as black cultivars with high antioxidants (Suarni et al, 2020). The antioxidant is active during the reproductive phase and causes a purplish to black color on the grains (Dwiatmini and Afza, 2018), so their tolerance to double stress is less optimal in the vegetative phase. The Salumpikit cultivar is a genotype only tolerant of drought stress.…”
Section: Discussionmentioning
confidence: 99%
“…The Jeliteng cultivars are known as black cultivars with high antioxidants (Suarni et al, 2020). The antioxidant is active during the reproductive phase and causes a purplish to black color on the grains (Dwiatmini and Afza, 2018), so their tolerance to double stress is less optimal in the vegetative phase. The Salumpikit cultivar is a genotype only tolerant of drought stress.…”
Section: Discussionmentioning
confidence: 99%
“…Masyarakat kini mulai mementingkan kesehatannya sehingga lebih menyeleksi bahan pangan yang dapat mencukupi kebutuhan gizi mereka (Utami, 2021). Padi fungsional merupakan bahan pangan pokok dengan kandungan gizi tinggi yang berguna untuk kesehatan (Dwiatmini & Afza, 2018). Selain memiliki kandungan energi, serat, protein, lemak, dan mineral, padi fungsional mengandung antosianin yang ditandai dengan adanya pigmen warna merah dan ungu pekat.…”
Section: Pendahuluanunclassified
“…Semakin tinggi kadar antosianin menimbulkan warna yang lebih pekat pada suatu bahan pangan (Sitanggang et al, 2018). Antosianin berfungsi sebagai antioksidan bagi tubuh (Dwiatmini & Afza, 2018). Padi merah dan padi hitam tergolong dalam padi fungsional.…”
Section: Pendahuluanunclassified
“…Pratiwi and Purwestri (2017) have documented 24 varieties of black rice from Java, Nusa Tenggara, Sulawesi and Kalimantan. Meanwhile, Dwiatmini and Afza (2018) have used 27 types of red rice originating from various regions in Indonesia such as Kalimantan, Java, Sumatra, Riau, and East Nusa Tenggara to conduct research on anthocyanin content in rice accessions. Afza (2016) reported that there were 54 accessions of brown rice preserved at the Center for Research and Development of Agricultural Biotechnology and Genetic Resources, Bogor.…”
Section: Introductionmentioning
confidence: 99%